Menumbuhkan Rasa Percaya Diri pada Anak Melalui Permainan Peran Bersama Mahasiswa Kesejahteraan Sosial Fisip USU - Neni Tresna Juliani Laia; Tuti Atika (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
Children are the nation's golden generation who will become the cornerstone of a country to be successful or not. During the developmental period of children, it is important for them to gain self-confidence. Good self-confidence will bring children to be able to explore something without feeling ashamed, insecure, or afraid. During the implementation of PKL II conducted by the writer at the Yayasan Panti Asuhan Sosial Bina Mandiri, Medan, the writer found a problem in a group of orphanage children. Confidence is their main problem, this is based on the results of observations of researchers while carrying out work practices. The author hereby seeks to help children to be able to grow their self-confidence, by using the group work method as an approach and in handling it the author applies role playing to encourage children to have self-confidence. The author believes that role play is effective for exploring and bringing back children's self-confidence. The author hopes that this role play can be one of the things that can be done as a way of solving their problems.